(untitled) (Conferencea, 2021)
Music is derived from the Greek word mousiche, and the art of miracles is an art form that reflects the range of human emotional experiences, thoughts, and imaginations through a sequence or combination of musical sounds (tones, melodies). There are various scientific hypotheses about the origin of music: emotional speech (G. Spencer), birds singing and animals calling their mates (Charles Darwin), primitive human labor methods (K. Buchaner) and K. Buchaner. ), sorcery (J. Combarrier) are the primary sources of music. Oriental thinkers have also made scientific comments on the origin of music. The history of music was explained by Farobi in connection with the process of formation of human speech and emotions, and Ibn Khaldun (14th century) - based on the laws of formation of social systems